Maqâshid al-Syarî`ah Paradigm for the Protection of Children Victims of Narcotics Abuse - Jamil, Syahril; Abdillah, Muhammad; Torik, Muhammad; Rostami, Soheila (Madania: Jurnal Kajian Keislaman, 2023)
Narcotics often cause children to become victims and it also affects the protection of children's rights. This study is intended to see how maqâshid al-syarî`ah views the protection of child victims of narcotics. The method used in this study was a descriptive qualitative approach to explore how paradigms, factors, and implications for the protection of child victims of narcotics. The data in this study was obtained through a search of a search engine google.com with the keyword "maqâshid al-syarî`ah paradigm towards legal protection of child victims of narcotics", then the data was reduced to present the expected results in this study. The analysis of this study shows that legal protection for children victims of narcotics has not been fulfilled; hence, it is not uncommon for children to be used as agents for the sustainability of narcotics trafficking in Indonesia. This study is based on an argument that the protection of children entangled in drug cases is still not optimally provided in terms of prevention, legal process, and punishment of child victims of narcotics. As a result, a maqâshid al-syarî`ah approach is required, to achieve an advantage in providing legal protection regulations for children who have been victims of narcotics in Indonesia. Narkotika seringkali menjadikan anak-anak sebagai korban, hal tersebut juga berimbas pada perlindungan atas hak-hak anak. Tulisan ini ditujukan untuk melihat bagaimana pandangan maqhasid al-Syariah terhadap perlindungan anak korban Narkotika. Tulisan ini menggunakan pendekatan kualitatif deskriptif untuk menelusuri bagaimana paradigma, faktor dan implikasi terhadap perlindungan anak korban narkotika. Data dalam tulisan ini didapati melalui penelusuran terhadap mesin pencari google.com dengan kata kunci “paradigma maqhasid al-Syariab terhadap perlindungan hukum anak korban narkotika”, selanjutnya data direduksi untuk dapat menghadirkan hasil yang diharapkan dalam tulisan ini. Tulisan ini menunjukkan belum terpenuhinya perlindungan hukum pada anak korban narkotika, sehingga tidak jarang anak-anak dijadikan sebagai agen demi keberlangsungan peredaran narkotika di Indonesia. Studi ini didasari pada satu argument bahwa perlindungan anak yang terjerat kasus narkotika masih belum maksimal diberikan baik dari pencegahan, proses hukum, dan hukuman terhadap anak korban narkotika. Untuk itu diperlukan suatu pendekatan maqâshid al-syarî`ah yang bertujuan untuk mencapai kemaslahatan dalam rangka menghadirkan regulasi perlindungan hukum pada anak korban narkotika di Indonesia.